An efficient deep learning approach to detect retinal disease using optical coherence tomographic images - Khan, Farhan Sakib; Ferdaus, Nowshin; Hossain, Tamim; Islam, Quazi Sabrina; Islam, Md. Iftakharul (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.